Karakterisasi Sistem Panas Bumi Non-Vulkanik pada Manifestasi Air Panas Biatan Bapinang: Studi Pendahuluan - Nanda Hanyfa Maulida; Octa Della Puspita; Akroma Hidayatika; Rahmi Mulyasari (OPHIOLITE: Jurnal Geologi Terapan, 2024)
The emergence of hot spring manifestations in Biatan Bapinang, East Kalimantan, is intriguing due to its location, far from active volcanic and tectonic regions. This study aims to investigate possible causes and characteristics of this geothermal system using geological analysis and Bouguer anomaly distribution. Regional geological data and a Digital Elevation Model (DEM) were used to examine rock formations and potential structures that could serve as pathways for hot fluid migration. Bouguer anomaly distribution provided insights into density variations associated with basement depth. Findings indicate that the Biatan Bapinang hot spring manifestation lies at the boundary between a sedimentary basin and a basement uplift. The fluid likely originates from the sedimentary basin, with basement uplift potentially enhancing heat flow that warms subsurface water. Lithological boundaries and possible subsurface structures create preferential pathways for hot fluids to reach the surface. This study suggests that the Biatan Bapinang geothermal system is a non-volcanic, intraplate basin-type system, with a probable heat source from terrestrial heat flow concentrated by the basement uplift and local geological configuration. This research opens opportunities for further studies on geothermal potential in non-volcanic regions, especially in the Biatan area.